The Practice Of Share Repurchase And Its Signaling Impact On Stocks Quoted On The Kuala Lumpur Stock Exchange (Klse) - Musir, Mohamad Nazri (2004)
Share repurchase is another alternative besides dividends for companies to distribute their cash. Past research have found that the share repurchase activities are done during rising markets and also have signaling impact whenever an announcement is made and it varies due to the size of the company. Share repurchase activities is considered quite a new phenomenon in Malaysia and our study is basically to find out whether the trend of share repurchase activities and the impact of announcement date as well as size is the same as past research done in overseas market.